Developing a clinical-pathological framework of long COVID-related fatigue applied to public safety workers - Lofrano-Porto, Adriana; D’Isabel, Susanne; Smith, Denise L. (Frontiers in Medicine, 2024)
In the wake of the COVID-19 pandemic, millions worldwide are still struggling with persistent or recurring symptoms known as long COVID. Fatigue is one of the most prevalent symptoms associated with long COVID, and for many it can be debilitating. Understanding the potential pathological processes that link fatigue to long COVID is critical to better guide treatment. Challenges with diagnosis and treatment are reviewed, recognizing that post-COVID fatigue does not always present with corroborating clinical evidence, a situation that is frustrating for both patients and healthcare providers. Firefighters are a group of public safety workers who are particularly impacted by long COVID-related fatigue. Firefighters must be able to engage in strenuous physical activity and deal with demanding psychological situations, both of which may be difficult for those suffering from fatigue. Disruption in public safety worker health can potentially impact community welfare. This review creates a framework to explain the clinical-pathological features of fatigue resulting from long COVID, addresses diagnosis and treatment challenges, and explores the unique impact fatigue may pose for public safety workers and their organizations.